The Impact of Didactics in Teaching Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Education as an integral part of cognitive activity, occurs on the basis of the general law of the individual's knowledge of the surrounding world. Therefore, it is necessary to carry out in one totality in the process of training, upbringing of the individual, as a harmonious generation. When a teacher is aware of the principles of education, he / she will be able to manage it effectively, choose the right effective methods of teaching. Therefore, the principles of teaching are the main negatives of solving the most important issues of the educational process from the theoretical and practical point of view. The article consists of theory, practice and result.